ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG - Fadli Faturrahman; Sudrajat Martadinata (Jurnal Riset Kajian Teknologi dan Lingkungan, 2021)
This research aims to find out the internal control system of merchandise inventory that the company applies in terms of internal control elements in accordance with the Committee of Sponsoring Organization.Analytical methods that research uses in analyzing, using qualitative methods with a literature study approach.The results showed that the internal control system of trade goods inventories implemented by the company was working well.The application of an internal control system for the supply of merchandise applied by the company related to the five elements of internal control based on the Committee of Sponsoring Organization, namely the environment of control, risk assessment, control activities, information and communication, and supervision, as a whole can be concluded that the application is effective.